Impact of nanohydroxyapatite on enamel surface roughness and color change after orthodontic debonding - Ajami, Shabnam (Prog Orthod, 2016)
BACKGROUND: The aim of this prospective in vitro study was to evaluate the effect of nanohydroxyapatite (nanoHAP) serum on the enamel surface roughness and tooth color stability after orthodontic debonding procedure. METHODS: The crowns of 30 premolars were embedded in acrylic blocks with a 4 mm × 5-mm-sized window on the middle third of buccal surfaces. Primary roughness values were evaluated by an atomic force microscope (AFM). After bracket debonding, and polishing procedures, the second roughness parameters were recorded. Specimens were then randomly assigned to two equal groups. NanoHAP serum and HAP toothpaste were applied for 10 days in the first and second groups, respectively. Then, after the third AFM, initial color parameters were measured. Following 1-week immersion in the coffee solution, second color assessment was performed. The fourth AFM was registered after 2 months of aging process. RESULTS: All roughness parameters were elevated following debonding procedure. There was no statistically significant reduction in roughness parameters after 10 days of nanoHAP serum or HAP toothpaste application. Both groups showed significant color change after immersion in the coffee solution. CONCLUSIONS: NanoHAP serum with the protocols used in this study could not restore enamel surfaces to their original condition.